Total Control – Pollen Presentation and Floral Longevity in Loasaceae (Blazing Star Family) Are Modulated by Light, Temperature and Pollinator Visitation Rates - Henning, Tilo (Public Library of Science, 2012)
Stamen movements can be understood as a mechanism influencing pollen presentation and increasing outbreeding success of hermaphroditic flowers via optimized male function. In this study we experimentally analyzed the factors regulating autonomous and thigmonastic (triggered by flower visitors) stamen movements in eight species of Loasaceae. Both types of stamen movements are positively influenced by light and temperature and come to a virtual standstill in the dark and at low temperatures (12°C). Pollen presentation is thus discontinued during periods where pollinators are not active. Overall stamen presentation increases with increasing flower age. Contrary to expectation, no geometrical correlation between the floral scale stimulated and the stamen fascicle reacting exists, indicating that the stimulus is transmitted over the receptacle and stamen maturation dictates which and how many stamens react. Thigmonastic stamen presentation is dramatically accelerated compared to autonomous movement (3–37 times), indicating that the rate of stamen maturation can be adjusted to different visitation schedules. Flowers can react relatively uniformly down to stimulation intervals of 10–15 min., consistently presenting comparable numbers of stamens in the flower c. 5 min. after the stimulus and can thus keep the amount of pollen presented relatively constant even under very high visitation frequencies of 4–6 visits/h. Thigmonastic pollen presentation dramatically reduces the overall duration of the staminate phase (to 1/3(rd) in Nasa macrothyrsa). Similarly, the carpellate phase is dramatically reduced after pollination, down to 1 d from 4 d. Overall flower longevity is reduced by more than 2/3(rds) under high visitation rates (<3 d versus 10 d under visitor exclusion) and depleted and pollinated flowers are rapidly removed from the pool. Complex floral behaviour in Loasaceae thus permits a near-total control over pollen dispensation schedules and floral longevity of the individual flower by an extraordinary fine-tuning to both biotic and abiotic factors.